Head and neck follicular dendritic cell sarcoma: disease associations and treatment review - Asha'ari, Zamzil Amin; Suhaimi, Y.; Raja Lope Ahmad, Raja Ahmad Al'konee (Malaysian Medical Associations, 2010)
Currently, of less than 50 cases of head and neck follicular dendritic cell (FDC) sarcoma reported in the literature, 5 have been found to occur in the background of Castleman disease.We report another case of head and neck FDC sarcoma with emphasise on its associated lesions and review the outcome of treatment from the existing cases in the literature.